Upaya Pembentukan Insan Kamil melalui Integrasi IMTAK dan IPTEK di SMK - Sulton Muzakki; Imam Junaris; Muhammad Ulul Azmi; Arju Mushaffa (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The integration of faith and piety (IMTAK) and science and technology (IPTEK) is important to implement in education to form a complete human being (insan kamil). The purpose of this study is to describe the forms of integration of IMTAK and IPTEK at SMK Maarif NU Mantup, describe the impact of IMTAK and IPTEK integration at SMK Maarif NU Mantup in shaping insan kamil, and describe the supporting and inhibiting factors of IMTAK and IPTEK integration. This research uses a qualitative approach with descriptive research type, which is to describe phenomena that occur in the field. The results of this study are: 1) The integration of IMTAK (faith and piety) and IPTEK (science and technology) at SMK Maarif NU Mantup is manifested by balancing the skills gained from each student's major with religious activities such as reading prayers together before class, performing Dhuha prayer, reading short surahs, congregational Dhuhr prayer, cultum (short religious lectures), special subjects, utilizing technology in religious lessons, and assessing both skills and religious abilities. 2) The impact felt in shaping a perfect human character includes changes in work skills and religious attitudes, such as discipline, good manners, devotion to worship, and control over gadget usage. 3) Supporting factors include the students' innate talents that make it easier for teachers to guide them, cooperation among teachers, and school policies, while hindering factors include student interactions that cannot be supervised by teachers and the lack of involvement of some parents in monitoring their children. Keywords: Faith and Piety, Insan Kamil, Science and Technology